Integration of Critical Reason in Islamic Civilization: A Solution to The Stagnation of Modern Islamic Education - Hidayatullah, Naufal; Mohammad Subhi Ibrahim (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2026)
Modern Islamic education now faces a serious challenge in the form of intellectual stagnation caused by the dichotomy of science and the dominance of taqlid culture. The stagnation of modern Islamic education is a real consequence of the neglect of critical reason. This research aims to formulate a model of critical reasoning integration as a solution to this intellectual confusion. Using a qualitative method of literature study with a philosophical-pedagogical approach, data was analyzed through the Miles and Huberman model which includes condensation, data presentation and conclusion drawn. The results of the study formulated an Integrative-Dialectical Epistemology Model that works through a cycle of deconstruction and then reconstruction of turats material. The contribution of this paper lies in the synthesis between classical Islamic epistemology and modern critical pedagogy that places critical reason not as a threat to faith, but rather as a strengthening of religious commitment through argumentative and philosophical understanding. Conceptually, this model can affect the repositioning of Muslims from consumers to knowledge producers. The systemic impact is the realization of a generation that is not only ritually pious, but also socially transformative and innovative in the global era